2016
DOI: 10.13189/sa.2016.041102
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mesoamerican Naked-eye Observation of Sunspots - V: Evidence from Río Azul Tomb I Murals and Related Artifacts

Abstract: Many cultures of antiquity have made naked-eye observations of large sunspot displays. The Chinese, Japanese, Koreans, and Greeks, have all made such observations. Pictorial evidence on dated Mesoamerican monuments suggests that similar observations may have been made in the New World as well. In this regard, Tomb 1 at Río Azul is of particular interest. Within the tomb, murals depict a spotted Sun God as the "father" of Tikal king "Curl Snout" (Yax Nuun Ayiin I). Therefore, the murals of Tomb 1 corroborate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Evidence of a previously unreported naked-eye sunspot observation in 1604 from a 17th century Hungarian history was presented by Simpson (2018). In addition, Zito (2016Zito ( , 2017 has presented some interesting results about possible Mesoamerican naked-eye observation of sunspots.…”
Section: Evaluation Of Historical Naked-eye Observations Of Sunspotsmentioning
confidence: 99%
“…Evidence of a previously unreported naked-eye sunspot observation in 1604 from a 17th century Hungarian history was presented by Simpson (2018). In addition, Zito (2016Zito ( , 2017 has presented some interesting results about possible Mesoamerican naked-eye observation of sunspots.…”
Section: Evaluation Of Historical Naked-eye Observations Of Sunspotsmentioning
confidence: 99%
“…Perhaps the artistic device of the spotted Sun God is simply a direct reflection of observed solar activity by Mayan priest/astronomers; although no direct evidence, such as a table of naked-eye sunspot observations, is known to exist [30,31]. Nevertheless, the presence of a spotted Sun God in Mayan art correlates with high solar activity, while the absence if cheek spots correlates with a quiet Sun [12,29,32,33,34]. The selection of Mayan artifacts for study has been dictated by four rules [12]: 1) the artistic motif must be present (Sun God with or without spots), 2) the artifact upon which the image occurs must be dated or dateable.…”
Section: Background To Mayan Astronomical Observationsmentioning
confidence: 99%
“…Furthermore, during solar conjunctions (or near conjunctions), deities other than the Sun God can receive a Sun God label (Kin sign marking), usually in the form of a tattoo on the God head. This was seen in report V, where a peccary was labelled with a kin sign in reference to the solar eclipse of April 27, 450 AD in which the Sun and the constellation of the peccary were closely spaced in the sky [1]. Therefore, the apparent "mislabeling" of the mask is not as unreasonable as one might at first think.…”
Section: The Jade Funerary Mask Of Rí O Azulmentioning
confidence: 92%
“…Previous papers of this series have shown that the spotted Sun God, or Sun God stand-in like Hun Ahau (one of the hero Headband Twins who becomes the Sun) [1], appear during times of the active Sun, while iconographic spots are absent during times of the quiet Sun. The connection between the spotted Sun God in the Early Classic Period (reports I, III, IV, V, and VI [2,3,4,1,5]) and Late Post-Classic Period (report II [6]) with physically observable and implied solar activity seems a reasonable conjecture. However, it is natural to ask, "What about other spotted deities?…”
Section: General Problem Statementmentioning
confidence: 96%